2005
DOI: 10.1111/j.1365-2141.2005.05702.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing adverse events in blood transfusion

Abstract: Summary Against a background of ever increasing expenditure on blood safety, less attention has been paid to improving the safety of the transfusion chain within hospitals. Based on reports to the Serious Hazards of Transfusion (SHOT scheme) between 1996 and 2003, the risk of an error occurring during transfusion of a blood component is estimated at 1:16 500, an ABO incompatible transfusion at 1:100 000 and the risk of death as a result of an ‘incorrect blood component transfused’ (IBCT) is around 1:1 500 000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 18 publications
0
61
0
3
Order By: Relevance
“…However, it is noteworthy that none of the six cases of mild clinical reactions in our study was reported actively but was revealed only by solicited feedback after the treating physicians had been questioned in the study follow-up by the blood service. This might indicate substantial underreporting of mild reactions in clinical practice and should remind the important part of transfusing physicians regarding to their responsibility in hemovigilance system [30]. In thrombocytopenic patients, in particular in hematooncology patients with concomitant neutropenia, bacterial contamination of blood products must be considered as one potential cause of febrile episodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that none of the six cases of mild clinical reactions in our study was reported actively but was revealed only by solicited feedback after the treating physicians had been questioned in the study follow-up by the blood service. This might indicate substantial underreporting of mild reactions in clinical practice and should remind the important part of transfusing physicians regarding to their responsibility in hemovigilance system [30]. In thrombocytopenic patients, in particular in hematooncology patients with concomitant neutropenia, bacterial contamination of blood products must be considered as one potential cause of febrile episodes.…”
Section: Discussionmentioning
confidence: 99%
“…ABOincompatible blood remains one of the leading causes of harmful or even fatal transfusion reactions reported to the national haemovigilance systems or governmental regulatory bodies, and human error accounts for most of these transfusion accidents. Following the successful implementation of screening tests for TTI markers and continuous improvement of test sensitivity and specificity, receiving the wrong RBC unit has become more likely than TTI (Sazama, 2003;Stainsby et al, 2005a;Stainsby et al, 2005bStainsby et al, , 2006 ( Fig 1). In the UK, this leads to an unacceptable and surprising number of ABO-incompatible transfusions every year (Fig 2) and haemovigilance systems in other countries show that this problem exists everywhere.…”
Section: Providing Enough Of the Right Blood To Each Patient In Needmentioning
confidence: 99%
“…HUS was the working diagnosis in the ED because of acute renal failure and hemolytic markers, but no evidence of thrombocytopenia and microangiopathic hemolytic anemia, which are classically observed in HUS (Razzaq, 2006), was observed in this patient. Our patient did have hemoglobinemia (Figure 1), but hemacommon foreign RBC antigens such as Rh, Kell, and Kidd (Stainsby et al, 2005). The eluate study in the appropriate clinical setting is diagnostic of DHTR (Engelfriet et al, 2006).…”
Section: Q: Besides Transfusions What Other Relevant Histories Shoulmentioning
confidence: 99%